Virome comparisons in wild-diseased and healthy captive giant pandas - Zhang, Wen; Yang, Shixing; Shan, Tongling; Hou, Rong; Liu, Zhijian; Li, Wang; Guo, Lianghua; Wang, Yan; Chen, Peng; Wang, Xiaochun; Feng, Feifei; Wang, Hua; et al. (Microbiome, 2017)
The giant panda (Ailuropoda melanoleuca) is a vulnerable mammal herbivore living wild in central China. Viral infections have become a potential threat to the health of these endangered animals, but limited information related to these infections is available.